(untitled) (Communication & Society, 2017)
Infographics as a transdisciplinary component that permits to objectify depth that amplifies and potentiates time and space, is the proper structure for the reading characteristics of Net Generation and outputs the dynamic skills of visual intelligence, creating mnemonic frameworks. This article analyses the use of its Informative content, and its appliance to the qualities of Online Information (accurate, timely, complete and concise), its components of Identity (periodicity, animation, stateness, interactivity, image, multimedia and typology) and its Informative components (structure, clarity, content and readability) through revision, over two weeks (2014 and 2015), of the six daily general online newspapers of Iberian Peninsula that, according to the Asociación para la Investigación de Medios de Comunicación and Marktest, have more views: El País, 20minutos, Público, Correio da Manhã, Jornal de Notícias and Diário de Notícias. Is also registered in this analysis, the vision of content producers through a survey of members of the Infographic Society (the only professional association of this particular profession established in the Iberian environment) and the results of the study are contrasted with an in-depth interview with structured questionnaire relating to four global infographic designers working for The Guardian, The Times and National Geographic. Although the results reflect a low Multimediality and Interactivity, the analysis finds that there is a sensory and affective effort Permanence and Narrative in the mnemonic meshing of skills in Journalistic Online Infographics limited by a poor Visibility of the Infographic compound given by the media, either by failure of Production, of Continuity, Informative, of Usability and/or integration.